Disruption in maritime chokepoints and their implications (maritime route) - Lim, Hoong Keat (Nanyang Technological University, 2022)
This report aims to study factors of maritime chokepoint disruptions and their implications for stakeholders of maritime players along the supply chain. Information contained in this report should interest maritime professionals from fleet ownership & management and commercial freight owners of tramp & liner shipping. As this report only focuses on sea routes, we only include factors that would immediately disrupt stakeholders’ operations or sales. Our literature review has categorized maritime chokepoint disruptions into chokepoint risk, maritime security, and ship loss risk. Primary research via methodology stated in CHAPTER 3 RESEARCH METHODOLOGY also covers our research gap for the lack of information for emerging chokepoint disruptions, i.e., increased vessel size, political sanctions, cybersecurity, and the COVID-19 pandemic. Our primary and secondary findings reflect the implications of chokepoint disruptions as economic losses from operation, market, and environmental costs. Our evaluation and analysis were for common and emerging chokepoint disruptions through quantitative and qualitative assessments collated from interviews and surveys. Mathematical formulas were derived to address different operational, market, and environmental costs to be considered for events of chokepoint disruptions. Our findings and discussions highlight chokepoint risk as to the primary concern for our interviewed participants, especially when it occurs in Panama Canal. Nevertheless, maritime operations were struck with uncertainties by the COVID-19 (Coronavirus disease) pandemic, leading to internal chokepoint disruptions from within the organization. Although primary research reflected slight effectiveness in combating emergencies faced by maritime chokepoint disruptions through proactive strategies, they still serve the merit in raising awareness for the maritime industry. Nonetheless, it highlights the importance of having reactive strategies to engage volatility faced during such events. Therefore, our recommendations dwell on having proactive and reactive measures. Proactive measures take on the form of technical and non-technical management. Technical management ensures the vessel’s seaworthiness to withstand fatigue from weather risk and chokepoint delay over machinery breakdown before transiting through primary chokepoints. Non-technical management propagates awareness and risk of maritime chokepoint disruptions, especially among the new joiners. Reactive action would take on an anticipative and reactive stand towards events of maritime chokepoint disruptions through scenario planning exercises. During an emergency of chokepoint disruptions, stakeholders could consider our Financial Decision Tools to relieve decision anxiety in the decision-making process.